Waveguide-coupled metal-clad cavity with integrated feedback stub. (10th July 2017) - Feng, Kaiyin; Nishimoto, Masaya; Yu, Chuanqing; Saylan, Sueda; Taylor, Richard J. E.; Tanemura, Takuo; Nakano, Yoshiaki
Abstract: We propose a wavelength-scale metal-clad III–V semiconductor cavity coupled to silicon-on-insulator (SOI) waveguide with integrated feedback stub for external tuning of the Q factor. We consider a typical wavelength-scale metal-clad InP/InGaAs cavity integrated on a SOI waveguide and demonstrate more than 5-fold Q -factor improvement in agreement with that predicted by the coupled-mode theory. From additional thermal analysis, we prove that improved heat dissipation can be realized by engineering the layer thicknesses without sacrificing much of the optical performance.